Dopustnost ustanovitve zemljiškega dolga na stavbni pravici - Brence, Simon (Podjetje in delo, 2013)
The right of superficies and the land charge are two new limited real rights, introduced in our legal system with the adoption of the Law of Property Code. Consequently neither the legal theory nor the legal practice have till today satisfactory answered the question whether, taking into account of the sense of both legal institutions, the land charge could be established on the right of superficies. Therefore the basic purpose of this article is to answer the question whether the establishment of the land charge on the right of superficies is admissible. In pursuit of the answer the paper elaborates on the nature of the right of superficies and its manifestations and argumentative confronts with substantive reasons which could prevent such a combination of these two rights. The paper is based on the Slovenian legal regulation in this field which in turn it compares with the German one.
Keywords: hipoteka; nepremičnine; pravice; stavbna zemljišča; zemljiški dolg